The Role of Bugis Women in Pre-Islamic Era as a Strengthening of Local Wisdom Culture - Andi Dwi Resqi Pramana; Nurlaelah Mahmud (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the role of Bugis women in the pre-Islamic era as strengtheners of local wisdom culture in South Sulawesi. Bugis women not only function as family members, but also as the main movers in various aspects of religion and culture. As the main madrasah for their children, through their expertise in oral traditions and cultural customs that they uphold, women play an important role in preserving and transmitting cultural values ​​to the next generation. In addition, they are active in managing natural resources, organizing social life, and involving themselves in traditional ceremonies that are markers of community identity. Thus, Bugis women make a significant contribution to maintaining and strengthening local wisdom, which is the foundation for the life of the Bugis community. This study uses qualitative methods with analysis of historical documents, interviews, and direct observation. The results of the study show that Bugis women have a significant contribution to strengthening cultural identity, both through ritual practice and in managing natural resources. Therefore, this article highlights the importance of the role of women in building and maintaining local wisdom that is characteristic of the Bugis community.